Tuberculosis extrapulmonar con compromiso peritoneal. Reporte de caso clínico y revisión de literatura - Gatica T., Consuelo; Garrido V., Paola; Subiabre G., José (Revista Hospital Clínico Universidad de Chile, 2017)
Extrapulmonary tuberculosis accounts for a significant proportion of tuberculosis cases worldwide (about 20-25% of the cases). Nevertheless, the diagnosis is often delayed or even missed due to insidious clinical presentation and poor performance of diagnostic tests. Peritoneal tuberculosis is due to the infection of Mycobacterium tuberculosis in the peritoneum. It represents 0.7% of total cases of tuberculosis. This disease can mimic malignancy specially in women, because of its clinical presentation with ascites, weight loss and similar radiological sings. The phenomenon of migration, the increased use of immunosuppressive therapy and the epidemic of AIDS have contributed to a resurgence of this disease. We present the clinical case of a Haitian woman who presented ascites, abdominal pain and weight loss with radiological signs that suggested peritoneal carcinomatosis, in which further studies of ascitic fluid showed elevated adenosindeaminase, a specific and sensitive finding for tuberculosis.